2020
DOI: 10.1186/s13550-020-00618-0
|View full text |Cite
|
Sign up to set email alerts
|

Added value of 68Ga-PSMA PET/CT for the detection of bone metastases in patients with newly diagnosed prostate cancer and a previous 99mTc bone scintigraphy

Abstract: Purpose: To investigate the added value and diagnostic accuracy of 68 Ga-PSMA PET/CT versus bone scintigraphy (BS) for bone metastasis detection at the primary staging of prostate cancer (PCa). Methods: Inclusion criteria involved consecutive patients with newly diagnosed intermediate-to high-risk PCa, who had undergone BS, mostly with supplementary SPECT/low-dose CT, and 68 Ga-PSMA-11 PET/CT within less than 3 months without therapy initiation between the two investigations. BS was evaluated according to clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…A study among 112 PCa patients demonstrated that [ 68 Ga]Ga-PSMA-11 PET/CT detects metastatic bone lesions in 10% of patients without metastases on skeletal scintigraphy. 38 These results are congruent with the data presented in chapter 2 of this thesis, in which nine patients with negative skeletal scintigraphy had PET positive bone lesions. Despite the fact that the conservative EAU guidelines still recommend preoperative staging with CT and skeletal | 199 scintigraphy in high-risk PCa patients, skeletal scintigraphy has been replaced by PSMA PET/CT in some hospitals in the Netherlands.…”
Section: Detection Of Bone Metastasessupporting
confidence: 89%
See 1 more Smart Citation
“…A study among 112 PCa patients demonstrated that [ 68 Ga]Ga-PSMA-11 PET/CT detects metastatic bone lesions in 10% of patients without metastases on skeletal scintigraphy. 38 These results are congruent with the data presented in chapter 2 of this thesis, in which nine patients with negative skeletal scintigraphy had PET positive bone lesions. Despite the fact that the conservative EAU guidelines still recommend preoperative staging with CT and skeletal | 199 scintigraphy in high-risk PCa patients, skeletal scintigraphy has been replaced by PSMA PET/CT in some hospitals in the Netherlands.…”
Section: Detection Of Bone Metastasessupporting
confidence: 89%
“…Although the first wave of PSMA-related publications focused on its value PCa patients with a BCR, a vast number of initial, mostly small retrospective studies followed and demonstrated promising results of [ 68 Ga]Ga-PSMA PET/CT in initial staging. [38][39][40][41] Subsequently, Hope et al performed a meta-analysis to clarify detection rate of [ 68 Ga]Ga-PSMA-11 PET/CT for lymph node detection in the setting of primary staging of PCa. 42 The study comprised five studies (n = 266 patients, mostly classified as having intermediate to high risk PCa).…”
Section: Psma Pet/ct In Newly Diagnosed Pca ('Primary Staging')mentioning
confidence: 99%
“…Many studies comparing PSMA to 99m Tc-MDP have used PMSA-labeled PET tracers such as 18 F-DCFPyL PET/CT 38 and 68 Ga. 25 , 39 These studies also reported a higher sensitivity in PSMA-labeled PET tracers compared with 99m Tc-MDP, with sensitivity ranging from 96% to 100% and that of MDP being as low as 73%. One of the limitations of comparing our study to the above is the use of different imaging modalities with different resolutions (superior resolution on PET/CT 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be superior to traditional bone scintigraphy (BS) as it allows for detection of lytic type and early marrow-based metastases in addition to osteoblastic-type metastases seen on BS [ 2 , 3 , 4 ]. In a recent study involving 112 prostate cancer patients, 68Ga-PSMA-11 PET/CT revealed bone metastases in 10% of the patients who were deemed to be non-metastatic on BS and in 36% of the patients with indeterminate BS [ 5 ]. 68Ga-PSMA-11 PET/CT is also valuable for identifying skeletal involvement in patients with biochemical failure after treatment [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%